Synthesis and physical-chemical properties of 6-(5-(1Н-tetrazole-1-ylmethyl)-4-R-1,2,4-triazole-3-ylthio)pyridin- 3-amines and 6-((5-(1Н-tetrazole-1-yl)methil-4-R-1,2,4-triazole-3-ylthio)pyridin-3-yl)-(alk,ar,heter)ylmethanimines - Hulina, Yu. S.; Kaplaushenko, A. G.; Гуліна, Юлія Сергіївна; Каплаушенко, Андрій Григорович (Zaporizhzhya state medical university, 2017)
Over the past decade the number of publications, that contain different aspects of chemistry and use of triazoles and tetrazoles have been doubled and continues to grow. Publications of recent years show that heterocycles with 1,2,3,4-teterazoles and 1,2,4-triazoles are biologically active compounds with a broad spectrum of action. This fact indicates the interest to these compounds as potential objects of modern pharmaceutical market, namely to those compounds which contain both heterocycles. Purpose – synthesis and establishment of physical-chemical properties of 6-(5-(1Н-tetrazole-1-ylmethyl)-4-R-1,2,4-triazole-3-ylthio) pyridin-3-amines and 6-((5-(1Н-tetrazole-1-yl)methil-4-R-1,2,4-triazole-3-ylthio)pyridin-3-yl)-(alk,ar,heter)ylmethanimines. Materials and methods. The melting point has been determined by capillary method. The elemental composition of compounds has been set with the help of elemental analyzer Elementar Vario L cube (CHNS). 1H NMR spectra of obtained compounds has been set with the help of Varian Mercury VX-200, solvent – DMSO-d6, internal standart – Tetramethylsilane. Chromatography-mass spectrometry studies have been conducted on gas-liquid chromatograph Agilent 1260 Infinity HPLC equipped with a mass spectrometer Agilent 6120. 5-(1H-Tetrazole-1-ylmethyl)-4-R-1,2,4-triazole-3-thioles were used as starting materials for 6-(5-(1Н-tetrazole-1-ylmethyl)-4-R- 1,2,4-triazole-3-ylthio)pyridin-3-amines. Synthesis of the compounds was carried out in a medium of propyl alcohol in the presence of 5-amino-2-chloropyridine. 6-((5-(1Н-tetrazole-1-yl)methil-4-R-1,2,4-triazole-3-ylthio)pyridin-3-yl)-(alk,ar,heter)ylmethanimines were obtained reacting 6-(5-(1Н-tetrazole-1-ylmethyl)-4-R-1,2,4-triazole-3-ylthio)pyridin-3-amines with the appropriate aldehydes (acetaldehyde, m-anisaldehyde, 2-hydroxybenzaldehyde, 3-fluorobenzaldehyde, 4-fluorobenzaldehyde, 4-diethylaminobenzaldehyd, hydroxynaphthalene) in the acetic acid medium. Results. 11 New compounds, which have not been described previously, were obtained during the synthetic studies. The computer prediction was performed using PASS online service, it was found that the synthesized 6-(5-(1Н-tetrazole-1- ylmethyl)-4-R-1,2,4-triazole-3-ylthio)pyridin-3-amines and 6-((5-(1Н-tetrazole-1-yl)methil-4-R-1,2,4-triazole-3-ylthio)pyridin-3-yl)- (alk,ar,heter)ylmethanimines are low-toxic compounds and exhibit a wide range of biological actions, which corresponds to literature data. Conclusions. The results of our work have confirmed the structure of the synthesized compounds, which indicates the possibility of their further use in biological studies. За останні десять років кількість публікацій, що містять різні аспекти хімії та використання тріазолів і тетразолів, подвоїлась і продовжує збільшуватись. Публікації свідчать, що гетероцикли з ядрами 1,2,3,4-тетразолу та 1,2,4-тріазолу доволі добре зарекомендували себе як біологічно активні сполуки з широким спектром дії. Цей факт вказує на інтерес до сполук, що містять обидва гетероцикли, як до потенційних об’єктів сучасного фармацевтичного ринку. Мета роботи – цілеспрямований синтез і встановлення фізико-хімічних властивостей 6-(5-(1Н-тетразол-1-ілметил)-4- R-1,2,4-тріазол-3-ілтіо)піридин-3-амінів та 6-((5-(1Н-тетразоло-1-іл)метилен-4-R-1,2,4-тріазол-3-ілтіо)піридин-3-іл)-(алк, ар,гетер)ілметанімінів. Матеріали та методи. Температуру плавлення визначили капілярним способом на приладі ПТП (М). Елементний склад сполук встановили на елементному аналізаторі Elementar Vario ЕL cube (CHNS). 1H ЯМР-спектри сполук записали за допомогою спектрометра Varian Mercury VX-200. Хромато-мас-спектральні дослідження здійснили на газорідинному хроматографі Agilent 1260 Infinity HPLC з обладнаним мас-спектрометром Agilent 6120. Для отримання 6-(5-(1Н-тетразол-1-ілметил)-4-R-1,2,4-тріазол-3-ілтіо)піридин-3-амінів як вихідні речовини використали 5-(1Н-тетразол-1-ілметил)-4-R-1,2,4-тріазол-3-тіоли. Синтез сполук здійснений в середовищі пропілового спирту у присутності 5-аміно-2-хлорпіридину. 6-((5-(1Н-тетразоло-1-іл)метилен-4-R-1,2,4-тріазол-3-ілтіо)піридин-3-іл)-(алк,ар,гетер)ілметаніміни отримані взаємодією 6-(5-(1Н-тетразол-1-ілметил)-4-R-1,2,4-тріазол-3-ілтіо)піридин-3-амінів із відповідними альдегідами (ацетальдегідом, м-анісовим альдегідом, 2-карбоксибензальдегідом, 3-фторбензальдегідом, 4-фторбензальдегідом, діетиламінобензальдегідом, гідроксинафталіном) у середовищі ацетатної кислоти. Результати. Під час синтетичних досліджень отримано 11 нових сполук, що не описані раніше. Під час комп’ютерного прогнозування, котре виконували за допомогою онлайн-сервісу PASS, вдалось встановити, що синтезовані 6-(5-(1Н-тетразол- 1-ілметил)-4-R-1,2,4-тріазол-3-ілтіо)піридин-3-аміни та 6-((5-(1Н-тетразоло-1-іл)метилен-4-R-1,2,4-тріазол-3-ілтіо) піридин-3-іл)-(алк,ар,гетер)ілметаніміни належать до малотоксичних сполук і проявляють широкий спектр біологічної дії, що, своєю чергою, відповідає науковим літературним даним. Висновки. Результати роботи підтверджують структуру синтезованих сполук, що свідчить про можливість надалі застосовувати їх у біологічних дослідженнях.
Синтез і фізико-хімічні властивості 6-(5-(1Н-тетразол-1-ілметил)-4-R-1,2,4-тріазол-3-ілтіо) піридин-3-амінів та 6-((5-(1Н-тетразоло-1-іл)метилен-4-R-1,2,4-тріазол-3-ілтіо)піридин-3-іл)- (алк,ар,гетер)ілметанімінів
Keywords: 1,2,4-triazole; 1H-tetrazole; synthesis; physical-chemical properties; 1,2,4-тріазол; 1H-тетразол; синтез; фізико-хімічні властивості